การพัฒนาหนังสือสวนสัตว์สามมิติด้วยเทคโนโลยีโลกเสมือนผสานโลกจริงบนระบบปฏิบัติการแอนดรอยด์ - Ditcharoen, Nadh; Ratthirom, Anupong (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2016)
Development of 3D Zoo Book using Augmented Reality Technology on Android Nadh Ditcharoen and Anupong Ratthirom รับบทความ: 15 เมษายน 2559; ยอมรับตีพิมพ์: 31 พฤษภาคม 2559 บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อนำเสนอวิธีการออกแบบและพัฒนาหนังสือสวนสัตว์แบบสามมิติด้วยเทคโนโลยีโลกเสมือนผสานโลกจริง (Augmented Reality) ที่แสดงโมเดลแอนิเมชั่นสามมิติของสัตว์ใน 9 ส่วนการแสดงของสวนสัตว์อุบลราชธานีจำนวน 21 โมเดลใช้งานบนระบบปฏิบัติการแอนดรอยด์ การพัฒนาหนังสือสวนสัตว์สามมิติ ประกอบด้วย 6 ขั้นตอนหลัก ได้แก่ 1) การออกแบบและพัฒนาโมเดล 2) การออกแบบและพัฒนามาร์คเกอร์ 3) การสร้างเสียงประกอบ 4) การรวมองค์ประกอบ 5) การพัฒนาแอพพลิเคชั่น และ 6) การสร้างไฟล์ติดตั้ง หนังสือสวนสัตว์สามมิตินี้พัฒนาด้วยโปรแกรม Autodesk Maya โปรแกรม Adobe Photoshop โปรแกรม Metaio Creator และภาษา Arel Script โมเดลทั้งหมดได้รับการตรวจสอบความถูกต้องและปรับแก้จนสมบูรณ์ทั้งด้านเนื้อหาและด้านการพัฒนาสื่อจากผู้เชี่ยวชาญของสวนสัตว์อุบลราชธานีและผู้เชี่ยวชาญด้านเทคโนโลยี ผลการทดสอบระบบและการศึกษาความพึงพอใจด้วยแบบสอบถามจากผู้ใช้จำนวน 55 คน พบว่า ค่าเฉลี่ยความพึงพอใจมีค่าเท่ากับ 4.17 ซึ่งอยู่ในระดับดี หนังสือสวนสัตว์สามมิตินี้ช่วยให้จดจำสัตว์ได้ง่ายขึ้น อำนวยความสะดวกแก่ผู้ใช้งานในการศึกษาเกี่ยวกับสัตว์ได้ทุกที่ทุกเวลา ทั้งยังช่วยส่งเสริมการท่องเที่ยวไทยได้อีกทางหนึ่ง คำสำคัญ: สื่อการเรียนรู้ หนังสือสามมิติ ระบบปฏิบัติการแอนดรอยด์ โลกเสมือนผสานโลกจริง Abstract This paper aimed to present the design and development of a three-dimension zoo book using augmented reality (AR) technology. The book was designed for running on an android device displaying 21 animation models of 9 animal show zones in Ubon Ratchathani Zoo. The design and development process comprised of 6 main modules: 1) the design and development of models, 2) the design and development of markers, 3) sound ripping and synthesis, 4) component integration, 5) the design and development of android application, and 6) application deployment. The 3D zoo book was developed using Autodesk Maya, Adobe Photoshop, Metaio Creator, and AREL Script. All 3D animations were examined and modified in terms of content, completeness and media development by experts of Ubon Ratchathani zoo and technological experts of Ubon Ratchathani University. The book and application was tested and evaluated by 55 users in terms of users’ satisfaction using the questionnaires. The results showed that the average of users’ satisfaction was 4.17 which was at the high level. This book can facilitate users in memorizing animals, learning about animals and their habitat anywhere anytime, as well as it can be an alternative way to promote tourism in Thailand. Keywords: Learning media, 3D book, Android, Augmented reality, Lapak Ponsel